-6b-8=19

Simple and best practice solution for -6b-8=19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6b-8=19 equation:


Simplifying
-6b + -8 = 19

Reorder the terms:
-8 + -6b = 19

Solving
-8 + -6b = 19

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + -6b = 19 + 8

Combine like terms: -8 + 8 = 0
0 + -6b = 19 + 8
-6b = 19 + 8

Combine like terms: 19 + 8 = 27
-6b = 27

Divide each side by '-6'.
b = -4.5

Simplifying
b = -4.5

See similar equations:

| 4g-6-9=3 | | 3=5-2a | | 8x-1=8(x-3) | | 5x+8(-4x-9)=-10(-2x-9)+26 | | x^2-6x-96=0 | | 2k-1=-5+3k | | 24x=24+7x | | -3(4p+4)-2(6-14p)-3(7+5p)=0 | | 2(-5U+10)+2u= | | 2-5a=-8 | | 7x+5x-38=95-7x | | 2k-1=-5+2k | | 5b-13=3b+1 | | t=6s+18.01 | | 5z+30=40 | | 5-3p+9=13p+8 | | 3f+2=5 | | 5-4p=11 | | (5x-1)(x-5)=0 | | 0=324+2*3.65*x | | 9-(x+6)=9x-7 | | 0.3x-2.9=4.7x+2.6 | | 9x^4-25x^3+16x^2=0 | | 4n+5n=27 | | -2x^2+17x-35=0 | | (10x-10)=(8x+14) | | -8+3r=-3+2r | | 6+x+6+x=6x | | -8x+11+9x=2+x+9 | | 10r=4r+12 | | 15-(3m-5)=32 | | t+10=7r-14 |

Equations solver categories